Effects of Glucomannan on the Sacculus Rotundus and Peripheral Blood Lymphocytes in New Zealand Rabbits during Aflatoxicosis - Emrah Sur; Hasan Hüseyin Dönmez; Murat Boydak; Mehmet Bozkurt Ataman (The Scientific World Journal)
This study was aimed to determine the effects of the glucomannan added to aflatoxin- (AF-) contaminated diet on the sacculus rotundus and peripheral blood lymphocytes of New Zealand rabbits by histological and enzyme histochemical methods. Twenty-four adult rabbits of both sexes were divided into four equal groups, namely, as control, glucomannan 0.2 g/day, AF 125 μg/kg/day, and glucomannan combined with AF. The animals in all groups were treated for 12 weeks by the above-mentioned diet. When compared to control, AF-treatment caused significant decrease in alpha-naphthyl acetate esterase- (ANAE-) positive peripheral blood lymphocyte (PBL) percentages. The addition of the glucomannan to AFcontaining diet recovered the adverse effects of AF on sacculus rotundus and increased the ANAE-positive PBL counts. These results suggested that glucomannan was effective against the negative effects of AF in rabbits.